A mechanism-based group-psychotherapy approach to aggressive behaviour in borderline personality disorder: findings from a cluster-randomised controlled trial. Issue 1 (14th December 2020) - Herpertz, S. C.; Matzke, B.; Hillmann, K.; Neukel, C.; Mancke, F.; Jaentsch, B.; Schwenger, U.; Honecker, H.; Bullenkamp, R.; Steinmann, S.; Krauch, M.; Bauer, S.; et al.
Abstract : Background: Aggressive behaviour is a prevalent and harmful phenomenon in patients with borderline personality disorder (BPD). However, no short-term, low-cost programme exists that specifically focuses on aggression. Aims: Attuning therapy modules to pathogenetic mechanisms that underlie reactive aggression in BPD, we composed a 6 week mechanism-based anti-aggression psychotherapy (MAAP) approach for the group setting, which we tested against a non-specific supportive psychotherapy (NSSP). Method: A cluster-randomised two-arm parallel-group phase II trial of N = 59 patients with BPD and overt aggressive behaviour was performed (German Registry for Clinical Trials, DRKS00009445). The primary outcome was the externally directed overt aggression score of the Modified Overt Aggression Scale (M-OAS) post-treatment (adjusted for pre-treatment overt aggression). Secondary outcomes were M-OAS irritability, M-OAS response rate and ecological momentary assessment of anger post-treatment and at 6 month follow-up, as well as M-OAS overt aggression score at follow-up. Results: Although no significant difference in M-OAS overt aggression between treatments was found post-treatment (adjusted difference in mean 3.49 (95% CI −5.32 to 12.31, P = 0.22), the MAAP group showed a clinically relevant decrease in aggressive behaviour of 65% on average (versus 33% in the NSSP group), with particularly strong improvement among those with the highest baseline aggression. Most notably, significant differences in reduction in overt aggression between MAAP and NSSP were found at follow-up. Conclusions: Patients with BPD and aggressive behaviour benefited from a short group psychotherapy, with improvements particularly visible at 6 month follow-up. Further studies are required to show whether these effects are specific to MAAP.